Efficient Method to Catch Adsorption Behavior: Understanding the Effect of Sodium Ions on Benzene/Thiophene Adsorption in Na‐FAU. Issue 2 (21st November 2021) - Zhou, Xinming; Su, Li; Si, Fang; Wang, Yajun; Zhang, Tianhao; Wang, Youhe; Yang, Chaohe; Fu, Hui
Abstract: In this paper, grand canonical Monte Carlo simulations are applied to study the adsorption performance of thiophene and benzene. Pure adsorption and binary adsorption are performed in all silica faujasite (FAU) and Na‐FAU zeolite combined with density distributions and radial distribution functions (RDF). A new method to describe the adsorption mechanism in FAU has been proposed. One adsorbate is fixed in the center of 12 ring (12C) or the center of supercage (CSC) as the reference point. Then, RDFs represent the probability to find other adsorbates in a shell at the distance r of the reference point. Thus, the adsorption sites appeared are obtained as several ring shape areas. The intersection points, especially with high occurrence possibilities, is regarded as the main adsorption sites, showing good agreement with density distribution. Comparing RDFs of sorbate‐12C and the location of Na ions, the curve of thiophene‐12C and the curve of Na‐12C overlap can be found, which means thiophene prefers to adsorb around Na ions. On this point, the reason why the separation property of Na‐FAU zeolites is better than that of all silica FAU zeolites can be clearly explained. Abstract : The adsorption of thiophene/benzene in FAU using GCMC has been studied. Under the effect of Na ions modification, separation property is greatly improved. Through RDFs analysis, adsorbates prefer to adsorb slightly closer to the center of supercage after metal modification. Besides, thiophene is more sensitive to Na ions while there is no obvious effect on benzene adsorption with low loading.